1984
DOI: 10.1289/ehp.8454243
|View full text |Cite
|
Sign up to set email alerts
|

Chelation of cadmium without increased renal cadmium deposition.

Abstract: Cadmium (Cd) is mainly accumulated in liver and kidney bound to metallothionein (MT) and excreted very slowly from the body. In chronic exposure, Cd is gradually transported from liver to kidney; the renal toxic effects appear when renal Cd concentration exceeds the critical concentration. In order to prevent the Cd-induced renal disease, it is important to control the movement of Cd to the kidney and its renal deposition. However, the chelation of Cd from liver is difficult because of the high affinity of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
2

Year Published

1986
1986
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
4
2
Order By: Relevance
“…However, since no change in renal MT content was observed upon treatment with DMS, MPA, MHA and MMA, it may be suggested that neither these thiol compounds synthesized any additional renal MT nor the renal MT once induced by Hg was dependent on the Hg status of the MT. The decrease in renal and hepatic MT accompanied by lowering in their Hg levels on treatment with MFA are not in agreement with the reported mode of action of MFA (Giroux & Lachmann 1983). Contrary to the present finding, Giroux & Lachmann (1983) found increased renal MT and Hg burden which might be due to the difference in two experimental protocols.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, since no change in renal MT content was observed upon treatment with DMS, MPA, MHA and MMA, it may be suggested that neither these thiol compounds synthesized any additional renal MT nor the renal MT once induced by Hg was dependent on the Hg status of the MT. The decrease in renal and hepatic MT accompanied by lowering in their Hg levels on treatment with MFA are not in agreement with the reported mode of action of MFA (Giroux & Lachmann 1983). Contrary to the present finding, Giroux & Lachmann (1983) found increased renal MT and Hg burden which might be due to the difference in two experimental protocols.…”
Section: Discussioncontrasting
confidence: 99%
“…However, DMS seems to remove Hg also via kidneys and to be the most effective owing to the presence of two adjacent-SH groups in the compound (Cherian 1984;Sharma et al 1987). However, DMS seems to remove Hg also via kidneys and to be the most effective owing to the presence of two adjacent-SH groups in the compound (Cherian 1984;Sharma et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations